PENGARUH PENDIDIKAN KESEHATAN TERHADAP SIKAP TENTANG DETEKSI DINI KANKER SERVIKS - Husna, Nikmatul; Asfeni, Asfeni; Tobing, Vella Yovinna (Jurnal Cakrawala Promkes, 2020)
Cervical cancer is the leading cause of death in developing countries. Prevention that can be done by doing early detection of cervical cancer. Usually, women need health education before practising their behaviour. The purpose of this study was to determine the effect of health education on the attitudes of productive married women in the early detection of cervical cancer in the working area of the Payung Sekaki public health care in Pekanbaru. This study uses a quasi-experimental design with pre and post-test without control. Thirty samples were taken using a non-probability sampling technique, namely purposive sampling, with a questionnaire as a data collection tool. Paired t-test results obtained p value= 0,001 which is <0.05 which means that there is a significant influence between health education with changes in the attitude of productive married women in conducting early detection of cervical cancer. It is expected that public health care staff should always provide information on early detection of cervical cancer using media and counselling, to improve life welfare and can change attitudes in the early detection of cervical cancer.